A method for finding the genetic map position of cloned DNA fragments - R. L. Metzenberg; J. N. Stevens; E. U. Selker; E. Morzycka-Wroblewska (Fungal Genetics Reports, 1984)
A method for finding the genetic map position of cloned DNA fragments